The Implementation and Challenges of YouTube at Islamic Kindergarten Schools - Budiyanti, Kurnia; Zaim, M.; Thahar, Harris Effendi (Aulad: Journal on Early Childhood, 2025)
YouTube is considered one of the most popular social media platforms for teaching. However, the implementation and challenges of YouTube have become part of teachers’ experience. Therefore, this study aimed to explore the implementation and challenges faced by kindergarten teachers during their experience using YouTube. The study was a case study research design. This research involved six female teachers of an Islamic kindergarten school. The data were collected through interviews. The researcher applied the phases of data collection, reduction, display, and verification to analyse the data. The results revealed that YouTube was used as a medium for teaching, even though they did not show YouTube to their students all the time. Moreover, the teachers designed new teaching after getting new ideas from YouTube. Besides, the findings also indicated the challenges such as inappropriate content and advertisement disturbances. The research findings have implications for the learning process in Islamic kindergarten schools, which is an effective platform for teachers to acquire creative ideas in teaching.